ANALISIS RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH PADA PT BANK RAKYAT INDONESIA (PERSERO), TBK. - Tasya Shafa Almira Sukmana, - (2021)
This study aims to determine the effect of Relationship Marketing which consists of several indicators, namely trust, commitment, communication, and conflict handling on customer loyalty at PT Bank Rakyat Indonesia (Persero), Tbk. Dissemination of data in this study through the distribution of questionnaires. Data analysis using simple linear regression test. This study obtained 110 respondents. This research data analysis tool uses the help of SPSS version 23. Based on the results of the research tests conducted, the results show that relationship marketing has a positive and significant effect on customer loyalty. Keywords: Relationship Marketing, Customer Loyalty.